A Morphological Analysis of Verb Derivation from Adjectives in Bugis, English, And Javanese: An Interlingual Perspective with a Cultural Dimension - Hengki Hengki; Ratna Ratna; Nehru Pasoloran Pongsapan (Journal of linguistics, culture and communication, 2026)
This study compares the morphological construction of verbs from adjectives in three typologically and genetically distinct languages: Bugis (Austronesian, spoken in South Sulawesi, Indonesia), Javanese (Austronesian, Central and East Java), and English. Using an interlingual and culturally informed approach, the study investigates 15 systematic adjective-verb pairings from different languages to find underlying derivational mechanisms, structural patterns, and the linguistic encoding of cultural values. The analysis shows unique morphological strategies: Bugis primarily uses verbalizing prefixes such as ma- and mam- often accompanied by phonological adjustments—demonstrating a tightly integrated system of affixation and reduplication; English relies heavily on zero derivation (conversion) and suffixation (e.g., -ize, -ify), reflecting its trend toward analyticity and syntactic flexibility; meanwhile, Javanese employs a complex system involving the prefix N- (with allomorphs like ng-, n-, m-) combined with the suf Crucially, the study shows that these morphological processes are not just grammatical, but also deeply embedded with cultural semantics—for example, the Bugis mappadeceng ("to act honestly") and Javanese ngresiki ("to cleanse inwardly") reflect ethical and communal values, implying that word formation serves as a linguistic vessel for cultural cognition. This study advances comparative linguistics by connecting Austronesian and Indo-European morphological typologies, enriches efforts in endangered language documentation (particularly for under-documented languages such as Bugis), and advances understanding of the language-culture interface in morphological derivation. The findings call for a more holistic approach to language research, in which structure and culture are studied together.